The Influence of Green Accounting, Environmental and Financial Performance on Company Value with Profitability as a Mediator - Nurlia; Adiyanti, Rini; Ardi, Muhammad (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2026)
This research aims to examine the extent to which the implementation of green accounting, environmental performance, and financial performance influences profitability and firm value in the basic materials sector listed on the Indonesia Sharia Stock Index (ISSI) during the period from 2019 to 2023. A quantitative approach with a descriptive design was applied. The data analyzed comprised 30 company observations representing 23 selected entities over five years. Data analysis techniques included simple and multiple linear regression through path analysis, Sobel test, and the calculation of the coefficient of determination. Hypothesis testing was conducted using t-test, F-test, and Sobel test, supported by EViews 12 Enterprise software. The findings indicate that green accounting significantly affects company profitability. In contrast, environmental performance and financial performance do not have a direct impact on profitability. However, when considered simultaneously, all three variables contribute to an increase in profitability. Additionally, the results show that environmental performance and profitability have a direct effect on firm value, while green accounting and financial performance do not exhibit a significant direct influence. Overall, all variables collectively influence firm value. Nevertheless, profitability does not act as a mediating variable in the relationship between green accounting, environmental performance, and financial performance on firm value.